Performance of DVB-T2 Application in High-Speed Train Transportation System - Tarigan, Nicolas Yonara; Pamungkas, Wahyu; Isnawati, Anggun Fitrian (Engineering, Technology & Applied Science Research, 2024)
The terrestrial television system in Indonesia has evolved from the first-generation Digital Terrestrial Video Broadcasting (DVB-T) to the second generation (DVB-T2), enhancing broadcast quality and spectral efficiency. This paper focuses on the application of DVB-T2 within High-Speed Train (HST) communication systems, where the unique challenges faced include high Doppler shifts and multipath effects due to the high train speed which exceeds 300 km/h. Multicarrier Orthogonal Frequency Division Multiplexing (OFDM) technology was employed along with 64-QAM modulation for the investigation of the performance under various conditions. The simulations were structured around varying speeds, scatterer counts, and angles, and 15 iterations were conducted for train speeds of 10 m/s, 50 m/s, and 100 m/s. The findings indicate that the error rates varied with speed and environmental complexity. At a lower speed (10 m/s), the system performance showed significant improvement, with a reduction of 322 bits in the error rate. However, as the speed increased to 100 m/s, the performance declined, demonstrating an increase of errors by 414 bits owing to exacerbated Doppler effects. Different scatterer counts also influenced the results. For instance, with four scatterers at 10 m/s speed, the error improved by 245 bits, but at 100 m/s speed and under the same scatterer conditions, the performance worsened, increasing the error by 361 bits.